Fracture Load of Layered Glass-Ceramic Structures - Marocho, S. M. Salazar; Cesar, P. F.; Griggs, J. A.; Bottino, M. A. [UNESP] (Springer Nature, 2022)
The mechanical behavior and failure mode of multilayered bonded and non-bonded glass-ceramic structures after long-term water-aging is relevant considering how widely used these ceramics are in many fields. This work is focused on ceramic structures used in dentistry. The objective here was to determine the fracture load of ceramic structures not bonded and bonded to a dentin analog material (G10) using low (L) and high-viscosity (UH) dual-cured resin cements (C). Porcelain (P) disks were tested whether bonded or not bonded to G10, as follows: a) P – control group, b) PHF – acid etched, c) P·CL – HF and coated with CL, d) P·CUH – HF and coated with CUH, e) P·CL·G10 – HF and bonded to G10 using CL, and f) P·CUH·G10 – HF and bonded to G10 using CUH. The groups bonded to G10 were stored in deionized water for 24 h, 1, 3, and 6 months. The fracture load was examined using Weibull statistics. The Weibull modulus (m) for group P was similar to that of PHF and significantly higher than for P·CL and P·CUH. P·CL showed higher m than P·CUH. As for the characteristic fracture loads (F0), P and PHF showed statistically similar values that were significantly higher than those obtained for P·CL and P·CUH. For P·CUH·G10, there was no effect of storage time on both the F0 and m. For P·CL·G10, storage time only caused significant changes in F0. After aging, there was no change in the mechanical behavior of the porcelain structures bonded to G10 using CUH. There was a decrease in F0 over time when CL was used. These results reveal that the viscosity of the resin cement plays an important role in the mechanical behavior of the bonded porcelain structures. Overall, ceramic structures bonded using a high-viscosity dual-cured resin cement seems to present better performance over time.
Keywords: bonding; fracture load; porcelain; resin cement; viscosity